Fabrication of polyamide hollow fiber nanofiltration membrane with intensified positive surface charge density via a secondary interfacial polymerization - Yin, Yurong (2023)
In this work, a positively charged hollow fiber nanofiltration (NF) membrane based on twice interfacial polymerization (IP) reactions was developed for water soften and heavy metal ions removal. The first IP reaction was conducted on the polyethersulfone (PES) hollow fiber substrate using a mixture of branched polyethyleneimine (PEI) and piperazine (PIP) as the aqueous phase monomers in the aqueous phase reacting with trimesoyl chloride (TMC) in the cyclohexane solution. Then, a secondary IP reaction was performed between tris(2-aminoethyl) amine (TAEA) solution and the residual acyl chloride groups on the membrane to increase the positive charge density on the membrane surface. Consequently, a NF membrane with intensified positive surface charge density was successfully fabricated. The optimized membranes achieved a high rejection of MgCl2 of 97.6% while maintaining a pure water permeability (PWP) of 16.0 L m−2 h−1 bar−1. Meanwhile, the membranes exhibit high rejection values of 99.8% to Cu2+ and 99.7% to Zn2+, respectively. In conclusion, this work provides a facile way to prepare a positively charged membrane for efficient water softening and metal ions removal.